Usability and Acceptability of a Computer-Based Social Communication Intervention for Persons with Traumatic Brain Injury: A Mixed-Methods Study - Meulenbroek, Peter; Cherney, Leora R. (Seminars in Speech and Language, 2022)
Computer-based interventions for persons with traumatic brain injury (TBI) are a rapidly developing treatment modality. However, the usability and acceptability of such treatments have not been thoroughly studied. We describe the user-experience of a computerized intervention in persons with TBI called the Work-Related Communication (WoRC) program. Two coders used qualitative analysis of semi-structured interviews to complete a thematic content analysis along with a cost–benefit analysis. Ten participants with severe TBI more than 1-year postinjury were interviewed. Seven participants were male, and three were female. Their mean age was 41.6 years (standard deviation: 13.1). All had 4 years of college or less and experienced severe TBIs. A qualitative analysis of the WoRC program usability resulted in the categories of Content (aspects of treatment approach), Interface (aspects of presentation), and Abilities (aspects of the cognitive disorder). WoRC program acceptability categories emerged as Specific (trained strategies can be applied to specific scenarios) and Personal (individual factors related to willingness to implement the trained strategies). The cost–benefit analysis demonstrated a 50.2% reduction in treatment costs, indicating that computer-enhanced interventions are a potentially cost-effective way to increase behavioral outcomes. We discuss these findings as they relate to future development of computer-enhanced programs for persons with TBI.
Keywords: traumatic brain injury; adult; communicative disorders; job re-entry; attitude to computer